DFT study of CO oxidation on Cu2O–Au interfaces at Au–Cu alloy surfaces. Issue 2 (3rd December 2014) - Liu, D.; Zhu, Y. F.; Jiang, Q.
Abstract : CO oxidation on the Cu2 O–Au interface at Au–Cu alloy surfaces. Abstract : Although Au–Cu alloy nanoparticles on inert substrates show high activity for catalyzing CO oxidation, the corresponding catalytic mechanism is not clear. To clarify the mechanism of this alloy catalysis method, CO oxidation reactions on Au–Cu alloy surfaces with different surface oxidation states are studied via density functional theory simulations. The simulation results indicate that on AuCu(111) and Cu2 O/Au3 Cu(111), CO and O2 cannot move together for reactions since they are adsorbed on separate Cu sites. On Cu2 O–Au/Au3 Cu(111), O2 prefers to be located at the Cu hollow sites near Cu2 O–Au interfaces. When CO diffuses to its neighboring Au sites, they can easily combine to generate CO2, for which the reaction barriers are no more than 0.42 eV. The Au and Cu synergetic effect for catalyzing CO oxidation can be realized on Cu2 O–Au interfaces at Au–Cu nanoparticle surfaces.